Comparison of Nebulized Versus Systemic Corticosteroid for Management of Children Presenting with Acute Exacerbation of Asthma - Ahmad, Ayaz; Khan, Zarmast; Javeed, Asif; Ali, Izhar; Wamiq, Saba; Khan, Iftikhar (Journal of Neonatal Surgery, 2025)
Introduction: Asthma is one of the most common chronic respiratory diseases in children, characterized by inflammation, bronchoconstriction, and mucus production in the airways, which leads to recurrent episodes of wheezing, coughing, and shortness of breath. Objective: The main objective of the study is to find the comparison of nebulized versus systemic corticosteroids for the management of children presenting with acute exacerbation of asthma. Methodology: This randomized controlled trial (RCT) was conducted at Department of Pediatric Medicine, Multan Medical & Dental College from March 2023 to September 2024. A total of 240 pediatric patients, aged 2 to 12 years were included in the study. Data were collected at baseline (upon presentation) and at multiple time points during treatment (12, 24, 48 hours, and discharge). The clinical severity of asthma exacerbations was assessed using the Pediatric Asthma Severity Score (PASS). Results: Both groups had a comparable mean age (6.4 ± 3.2 years vs. 6.3 ± 3.1 years, p = 0.75) and similar asthma severity as measured by the Pediatric Asthma Severity Score (PASS) (10.2 ± 2.5 vs. 10.1 ± 2.3, p = 0.85). Baseline respiratory rate, oxygen saturation, and gender distribution were also similar between the groups, with no statistically significant differences (p > 0.05 for all comparisons).At 48 hours, 85% of patients in the systemic corticosteroid group showed significant clinical improvement (PASS <4), compared to 68% in the nebulized corticosteroid group (p = 0.01), indicating a greater proportion of patients achieving symptom resolution in the systemic group. Conclusion: It is concluded that systemic corticosteroids provide more rapid clinical improvement and faster symptom resolution compared to nebulized corticosteroids in children with acute asthma exacerbations.